PENGARUH LAYANAN KONSELING INDIVIDU TERHADAP KESEHATAN MENTAL WARGA BINAAN WANITA (Kasus Non Narkoba) DI LAPAS ANAK PEKANBARU - Evi Apriyani; Zulfan Saam; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the effect of individual counseling on the mental health of non-drug women in the prisons of Pekanbaru children. The research method used is experimental research which analyzed descriptively qualitative analysis. The subjects were taken using purposive sampling as many as 5 non-drug cases women in prisons of Pekanbaru children. The research design used by the researcher is pre-test post-test one group design, which is done twice before before treatment or treatment (pre-test) and after treatment or treatment (post-test) with one group of subjects. This research is conducted by providing individualized counseling services that have been modified for 5 meetings. The results of this study indicate that there is influence individual counseling on mental health of non-drug women in the prisons of children Pekanbaru based on the results of questionnaire analysis and observations made by researchers. Before the counseling process ended, 2 non-drug women in non-drug cases in Lapas anak Pekanbaru were declared free (Drop Out).Keywords: Individual Counseling, Mentally Health, LAPAS